Milk Fat Globule-EGF Factor 8, Secreted by Mesenchymal Stem Cells, Protects Against Liver Fibrosis in Mice - An, Su Yeon; Jang, Yu Jin; Lim, Hee-Joung; Han, Jiyou; Lee, Jaehun; Lee, Gyunggyu; Park, Ji Young; Park, Seo-Young; Kim, Ji Hyang; Do, Byung-Rok; Han, Choongseong; Park, Hee-Kyung; et al. (Gastroenterology (New York, N.Y. 1943), 2017)
Mesenchymal stem cells (MSCs) mediate tissue repair and might be used to prevent or reduce liver fibrosis. However, little is known about the anti-fibrotic factors secreted from MSCs or their mechanisms. Umbilical cord-derived MSCs (UCMSCs) were differentiated into hepatocyte-like cells (hpUCMSCs), medium was collected, and secretome proteins were identified and quantified using nanochip-liquid chromatography/quadrupole time-of-flight mass spectrometry. Liver fibrosis was induced in mice by intraperitoneal injection of thioacetamide or CCl ; some mice were then given injections of secretomes or proteins. Liver tissues were collected and analyzed by histology or polymerase chain reaction array to analyze changes in gene expression patterns. We analyzed the effects of MSC secretomes and potential anti-fibrotic proteins on transforming growth factor β 1 (TGFβ1)-mediated activation of human hepatic stellate cell (HSC) lines (hTert-HSC and LX2) and human primary HSCs. Liver tissues were collected from 16 patients with liver cirrhosis and 16 individuals without cirrhosis (controls) in Korea and analyzed by immunohistochemistry and immunoblots. In mice with fibrosis, accumulation of extracellular matrix proteins was significantly reduced 3 days after injecting secretomes from UCMSCs, and to a greater extent from hpUCMSCs; numbers of activated HSCs that expressed the myogenic marker α-smooth muscle actin (α-SMA, encoded by ACTA2 [actin, alpha 2, smooth muscle]) were also reduced. Secretomes from UCMSCs, and to a greater extent from hpUCMSCs, reduced liver expression of multiple fibrotic factors, collagens, metalloproteinases, TGFβ, and Smad proteins in the TGFβ signaling pathways. In HSC cell lines and primary HSCs, TGFβ1-stimulated upregulation of α-SMA was significantly inhibited (and SMAD2 phosphorylation reduced) by secretomes from UCMSCs, and to a greater extent from hpUCMSCs. We identified 32 proteins in secretomes of UCMSCs that were more highly concentrated in secretomes from hpUCMSCs and inhibited TGFβ-mediated activation of HSCs. One of these, milk fat globule-EGF factor 8 (MFGE8), was a strong inhibitor of activation of human primary HSCs. We found MFGE8 to down-regulate expression of TGFβ type I receptor by binding to α β integrin on HSCs and to be secreted by MSCs from umbilical cord, teeth, and bone marrow. In mice, injection of recombinant human MFGE8 had anti-fibrotic effects comparable to those of the hpUCMSC secretome, reducing extracellular matrix deposition and HSC activation. Co-injection of an antibody against MFGE8 reduced the anti-fibrotic effects of the hpUCMSC secretome in mice. Levels of MFGE8 were reduced in cirrhotic liver tissue from patients compared with controls. MFGE8 is an anti-fibrotic protein in MSC secretomes that strongly inhibits TGFβ signaling and reduces extracellular matrix deposition and liver fibrosis in mice.